Distanciamiento empresarial: riesgo de “contagio” en alianzas y fusiones - Poirier-Garneau, Vincent (2020)
Cooperation agreements and mergers and acquisitions are frequent operations that enable the achievement of efficiencies. However, the resulting increase in market concentration could lead to a reduction (or elimination) of competitive pressures, among other aspects. For this reason, it is necessary for the competition authorities to carry out a thorough evaluation, but at the same time, within the parameters of reasonableness, before approving a transaction of this caliber, both in normal times and in times of crisis.In this article, the authors analyze various alternatives of inorganic growth through national, regional and comparative experience, in order to present the importance of a careful operation structuring along with the implementation of competition best practices, conditions that must be maintained in both normal times and in critical times such as the one that is experienced by the COVID-19.